Systematic Literature Review: Methods for Measuring Good University Governance Based on University Performance Assessment - Deka Veronica; Sri Rahayu; Yudi Yudi; Netty Herawaty (Cita konsultindo, 2024)
Abstract This study aims to conduct a systematic literature review (SLR) on methods for measuring Good University Governance (GUG) based on university performance assessment aspects. This review analyzes various measurement methods used in the literature to assess university performance and how these methods can be applied to measure GUG. The study employs an SLR methodology with steps including literature search in various academic databases, study selection based on inclusion and exclusion criteria, and thematic analysis to identify main themes and trends in the literature. Initially, the search was limited to 178 journals. After the review, 161 journals remained, and a further screening based on inclusion and exclusion criteria resulted in 34 suitable journals. Therefore, this systematic literature review will reveal methods used to evaluate university performance and identify optimization algorithms and fuzzy comprehensive indicators in the GUG framework used as evaluation methods for assessing performance evaluation methods.